Understanding Users To Adopt Cloud Computing Technology - Brenda Karisoh, Hensy Watung, Putri Ante (International Journal of Information Technology and Education, 2021)
This research is entitled "Factors that influence users to adopt cloud computing technology" which aims to examine what factors influence users in adopting or using cloud computing. This study focuses on the variables of Security, Internet Connection Quality, Attitudes towards Use and also the two variables contained in the Technology Acceptance Model (TAM). This study takes a sample of users who have used cloud computing in Yogyakarta. Samples of respondents were taken using accidental sampling technique, from all available 150 questionnaires, which can be returned and processed as many as 116 samples. Tests were carried out using the SmartPLS ver 2.0 program. Of the six hypotheses tested in this study, it finally showed significant results. The hypothesis shows that all of the variables proposed in this study affect user behavior in using cloud computing services.